Reflections on the Sahyādrikhaṇḍa’s Uttarārdha - Levitt, Stephan Hillyer (Studia Orientalia Electronica, 2017)
This paper provides a brief review of Gajanan Shastri Gaitonde’s corrected edition of J. Gerson Da Cunha’s 1877 text for the Sahyādrikhaṇḍa. It covers the import of O’Hanlon (2013) on the dating of various sections of the Sahyādrikhaṇḍa’s uttarārdha and the support it gives to earlier conclusions by Levitt. Furthermore, it covers the fragmentary text of Sahyādrikhaṇḍa uttarārdha 15, which, it turns out, is about Sārasvata Brahmans at a much earlier date, and the import that this chapter’s generally fragmentary state has with regard to the transmission of the Sahyādrikhaṇḍa. Finally, it briefly discusses the topic of the Pātityagrāmanirṇaya, a separable section of the Sahyādrikhaṇḍa’s uttarārdha, and the historical nature of the text. My edition and translation of this have recently been released by Motilal Banarsidass as no. 6 in their Hindu Tradition Series.